MAGNETOHYDRODYNAMICS FLOW OF A FREE CONVECTIVE DUSTY FLUID BETWEEN TWO PARALLEL OSCILLATING VERTICAL POROUS PLATES WITH DISSIPATIVE EFFECTS - Lawal, Olwafemi Waheed; Sottin, Osewanu D.; Babatunde, Sikiru A. (FUDMA Journal of Sciences, 2024)
This research investigates the unsteady Magnetohydrodynamics (MHD) flow of a free convective dusty fluid between two parallel oscillating vertical porous plates with dissipative effects. The dusty fluid is thought to be moving along the infinite plates as a result of an outside magnetic force. The temperature, velocity and pressure of the particles flowing along the channel are kept constant. The non-linear PDEs that govern the flow of the fluid are solved numerically using finite difference method and Maple 23 is used to implement and simulate the obtained scheme. The result are analyzed and presented inform of graphs. It is established that the effect of Reynolds number, viscoelastic parameter and Prandtl number on the velocity and temperature distribution are subdued by magnetic field.